Electroclinical Features and Long-term Seizure Outcome in Patients With Eyelid Myoclonia With Absences. (3rd May 2022) - Cerulli Irelli, Emanuele; Cocchi, Enrico; Ramantani, Georgia; Caraballo, Roberto H.; Giuliano, Loretta; Yilmaz, Tulay; Morano, Alessandra; Panagiotakaki, Eleni; Operto, Francesca F.; Gonzalez Giraldez, Beatriz; Silvennoinen, Katri; Casciato, Sara; et al.
Abstract : Background and Objectives: Eyelid myoclonia (EM) with absences (EMA) is a generalized epilepsy syndrome with a prognosis and clinical characteristics that are still partially undefined. We investigated electroclinical endophenotypes and long-term seizure outcome in a large cohort of patients with EMA. Methods: In this multicenter retrospective study, patients with EMA with ≥5 years of follow-up were included. We investigated prognostic patterns and sustained terminal remission (STR), along with their prognostic factors. Moreover, a 2-step cluster analysis was used to investigate the presence of distinct EMA endophenotypes. Results: We included 172 patients with a median age at onset of 7 years (interquartile range [IQR] 5–10 years) and a median follow-up duration of 14 years (IQR 8.25–23.75 years). Sixty-six patients (38.4%) displayed a nonremission pattern, whereas remission and relapse patterns were encountered in 56 (32.6%) and 50 (29.1%) participants. Early epilepsy onset, history of febrile seizures (FS), and EM status epilepticus significantly predicted a nonremission pattern according to multinomial logistic regression analysis. STR was achieved by 68 (39.5%) patients with a mean latency of 14.05 years (SD ±12.47 years). Early epilepsy onset, psychiatric comorbid conditions, and a history of FS and generalized tonic-clonic seizures were associated with a lower probability of achieving STR according to a Cox regression proportional hazards model. Antiseizure medication (ASM) withdrawal was attempted in 62 of 172 patients, and seizures recurred in 74.2%. Cluster analysis revealed 2 distinct clusters with 86 patients each. Cluster 2, which we defined as EMA-plus, was characterized by an earlier age at epilepsy onset, higher rate of intellectual disability, EM status epilepticus, generalized paroxysmal fast activity, self-induced seizures, FS, and poor ASM response, whereas cluster 1, the EMA-only cluster, was characterized by a higher rate of seizure remission and more favorable neuropsychiatric outcome. Discussion: Early epilepsy onset was the most relevant prognostic factor for poor treatment response. A long latency between epilepsy onset and ASM response was observed, suggesting the effect of age-related brain changes in EMA remission. Last, our cluster analysis showed a clear-cut distinction of patients with EMA into an EMA-plus insidious subphenotype and an EMA-only benign cluster that strongly differed in terms of remission rates and cognitive outcomes.